2017
DOI: 10.1016/j.msea.2016.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Grain coarsening behaviour of solution annealed Alloy 625 between 600–800 °C

Abstract: As with all alloys, the grain structure of the nickel-base superalloy 625 has a significant impact on its mechanical properties. Predictability of the grain structure evolution in this material is particularly pertinent because it is prone to inter-metallic precipitate formation both during manufacture and long term or high temperature service. To this end, analysis has been performed on the grain structure of Alloy 625 aged isothermally at temperatures between 600-800 • C for times up to 3000 hours. Fits made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Although there are many studies in the literature on alloy IN625, most of the reports are about wrought alloy IN625 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. So, studies on cast alloy IN625, such as the one presented in this paper, is needed to investigate its potential application in A-USC power plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are many studies in the literature on alloy IN625, most of the reports are about wrought alloy IN625 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. So, studies on cast alloy IN625, such as the one presented in this paper, is needed to investigate its potential application in A-USC power plants.…”
Section: Introductionmentioning
confidence: 99%
“…According the studies on wrought alloy IN625, the δ phase is observed to precipitate easily after long-term aging at 700-760 • C (the service temperature of A-USC power plants) [9][10][11][12][13], although it is initially designed as a solid solution hardening alloy [14]. The δ phase is an equilibrium phase corresponding to the γ phase with a composition of Ni 3 Nb and an orthorhombic (D0 a ) crystal structure [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The value of core diffusion activation energy (Q(core)) for Nickel reported from Frost and Ashby [39] was 170 kJ/mol. Moore et al [40] found different values of self-diffusion activation energy for where B0 is a structure-dependent constant,  is the applied stress, R is the ideal gas constant, and T is the test temperature. The value of core diffusion activation energy (Q(core)) for Nickel reported from Frost and Ashby [39] was 170 kJ/mol.…”
Section: Creep Testsmentioning
confidence: 99%
“…The value of core diffusion activation energy (Q(core)) for Nickel reported from Frost and Ashby [39] was 170 kJ/mol. Moore et al [40] found different values of self-diffusion activation energy for The value of core diffusion activation energy (Q (core) ) for Nickel reported from Frost and Ashby [39] was 170 kJ/mol. Moore et al [40] found different values of self-diffusion activation energy for the Inconel 625 alloy according to the temperature.…”
Section: Creep Testsmentioning
confidence: 99%
“…Because Nb element precipitate δ phase intergranular besides grain boundary carbides precipitation and it forms many peaks in scanning result. At750°C aging process, compared with ferrous Alloy 625, γ'' 'phase precipitation and γ'' →δ phase is delayed, which have good organizational stability [8,19,20]. In the process of aging, the generation and evolution of γ'' phase, δ phase, precipitation in the grain boundary and alloy element in the grain boundary affects the performance of the alloy [10,21,22].…”
Section: Alloy 625 Structure In Aging Processmentioning
confidence: 99%